2017
DOI: 10.1126/science.aaf9739
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Jagged complex structure implicates a catch bond in tuning ligand sensitivity

Abstract: Notch receptor activation initiates cell fate decisions, and is distinctive in its reliance on mechanical force and protein glycosylation. The 2.5 angstrom crystal structure of the extracellular interacting regions of Notch1 complexed with an engineered, high-affinity variant of Jagged1 (Jag1) reveals a binding interface that extends ∼120 angstroms along five consecutive domains of each protein. O-Linked fucose modifications on Notch1 EGF domains 8 and 12 engage the EGF3 and C2 domains of Jag1, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
326
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(332 citation statements)
references
References 46 publications
5
326
1
Order By: Relevance
“…Previous studies have revealed structures of EGF modified by O-fucose and O-glucose glycans (37)(38)(39). We superimposed the current structure of trisaccharide-modified hFA9 with an O-glucose monosaccharide-modified or an O-glucose disaccharide-modified EGF12, and we found that they align well with an r.m.s.d.…”
Section: Structural Analysis Of Hfa9 Egf Repeat Modified With Oglucosmentioning
confidence: 65%
See 2 more Smart Citations
“…Previous studies have revealed structures of EGF modified by O-fucose and O-glucose glycans (37)(38)(39). We superimposed the current structure of trisaccharide-modified hFA9 with an O-glucose monosaccharide-modified or an O-glucose disaccharide-modified EGF12, and we found that they align well with an r.m.s.d.…”
Section: Structural Analysis Of Hfa9 Egf Repeat Modified With Oglucosmentioning
confidence: 65%
“…Highly ordered O-linked sugar modifications may also be important for molecular recognition because O-linked sugars may work as "surrogate amino acids" in a given protein structure. For example, O-fucose glycans attached to EGF8 and EGF12 of Notch1 interact with the underlying amino acids and form a part of the Notch ligand-binding surface (37)(38)(39)(40). O-Glucose glycans on Notch are not required for Notch-ligand binding (8,16), which is supported by recent co-crystallized structures of Notch1 with ligands (37,38).…”
Section: O-glycans Modulate Egf Protein Stabilitymentioning
confidence: 81%
See 1 more Smart Citation
“…Ligand-specific control of signaling strength may be obtained by posttranslational modifications (68), protein clustering, and localization (69). It was recently demonstrated that different force requirements are needed to activate Notch signaling by different ligands and the authors suggest that this may be a mechanism for Notch-expressing cells to tune their sensitivity to discriminate between different ligands (70). It is possible that a binding between Jagged and vimentin acts as a force-generating mechanism to ensure efficient Jagged-Notch activation.…”
Section: Discussionmentioning
confidence: 99%
“…• The response of cell adhesion complexes to mechanical forces is diverse, [29][30][31]. Phenomenological theories, based on two state models [32,33], and microscopic theory [34,35] …”
Section: Discussionmentioning
confidence: 99%